2020
DOI: 10.1177/2325967120954417
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Musculocutaneous Nerve and Its Twigs to the Coracoid Process: An Operative Exposure

Abstract: Background: A musculocutaneous nerve (MCN) injury is a rare complication of the Latarjet procedure. Most of these injuries are neurapraxias and resolve with time; however, permanent injuries can occur. Understanding the anatomy and relationship of the MCN to the coracoid process is essential to prevent injuries. Purpose: To provide realistic, in situ–referenced measurements for the Latarjet procedure. Study Design: Descriptive laboratory study. Methods: A total of 12 matched-pair cadaveric specimens (24 fresh-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Α total of 126 studies were identified, 28 of which were assessed as full-text articles (Figure 1). Out of these, 23 manuscripts (1,2,15,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) were used for estimation of the MCN's typical course, 10 (6, 12, 15, 17, 27, 34, 36, 39-41) for calculation of the distance between the CP and the entrance point of the MCN into the CB, and 7 (2,6,12,15,17,36,40), for computation of the distance between the CP and the point of origin of the proximal branches.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Α total of 126 studies were identified, 28 of which were assessed as full-text articles (Figure 1). Out of these, 23 manuscripts (1,2,15,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) were used for estimation of the MCN's typical course, 10 (6, 12, 15, 17, 27, 34, 36, 39-41) for calculation of the distance between the CP and the entrance point of the MCN into the CB, and 7 (2,6,12,15,17,36,40), for computation of the distance between the CP and the point of origin of the proximal branches.…”
Section: Resultsmentioning
confidence: 99%
“…of CP-MCN penetration into the CB is frequently recorded as between 5-8 cm (1,3,12,13). In addition, MCNs with higher penetration into the CB have also been reported (14)(15)(16)(17). The current study reviews the data literature and estimates the prevalence of the MCN's typical course through the CB.…”
Section: Clinical Medicinementioning
confidence: 86%
See 1 more Smart Citation
“…In addition, the lateral root duplication was observed in 3 upper limbs unilaterally (11.1%, 3/27) by the current case series, while Pandey and Shukla [22] recorded a lower prevalence of 4.65% (8/172 cadavers). Some studies recorded the presence of accessory branches originating at a high-level position from the MCN main trunk [10,17,25]. Although this research point needs further investigation from larger clinical studies, surgeons need to know this correlation when operating, as the MCN lesions result in reduced elbow exion strength and sensory impairment of the forearm radial aspect.…”
Section: Discussionmentioning
confidence: 99%